Undermining Value-Based Purchasing — Lessons from the Pharmaceutical Industry - Dafny, Leemore S; Ody, Christopher J; Schmitt, Matthew A (The New England journal of medicine, 2016)
Although it's not yet clear how health care providers will respond to value-based payment models, an examination of pharmaceutical industry practices can provide insights into problems that may arise — and practices to avoid. In 2015, the U.S. Department of Health and Human Services announced a goal of linking at least 50% of Medicare spending to value-based payment models such as accountable care organizations. 1 Health care providers are now scrambling to reorganize in a way that delivers value while preserving or enhancing commercial success. Although it’s not yet clear how providers will respond to value-based payment models, an examination of pharmaceutical industry practices can provide insights into problems that may arise — and practices to avoid. Value-based plan design — a term that describes payers’ efforts to align consumer cost sharing with the value . . .